60 Geo. III, Chap. 2 at Hansard, Parliamentary Debates, 41:1647-52. - (:unkn) unknown (My University, 1820)
authorized judges "to arrest and detain any person carrying arms in such manner and at such times as, in the judgment of such magistrate, to afford just grounds of suspicion that the same are carried for purposes dangerous to the public peace?"
Keywords: PROTECED CARRY